2017
DOI: 10.1007/s40192-017-0103-6
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Properties of a Ni-Based Superalloy via Modification of the Forging Process: an ICME Approach to Fatigue Performance

Abstract: Traditionally, material design and property modifications are usually associated with compositional changes. Yet, subtle changes in the manufacturing process parameters can also have a dramatic effect on the resulting material properties. In this work, an integrated computational materials engineering (ICME) framework is adopted to tailor the fatigue performance of a Ni-based superalloy, RR1000. An existing fatigue model is used to identify microstructural features that promote enhanced fatigue life, namely a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 72 publications
2
9
0
Order By: Relevance
“…This result is in agreement with past measurements of slip band length in coarse grain RR1000 materials. 22 Moreover, these observations are consistent with the fatigue modeling results, whereas the formation of longer PSBs represented a higher degree of stored energy and were attributed to a shorter fatigue life. 22 Lastly, fatigue crack initiation has been observed extensively throughout the years at or near twin boundaries, stemming back to the work of Boettner et al 28 and Thompson 29 and more recently in Nibased superalloys.…”
Section: Strain Mappingsupporting
confidence: 86%
See 3 more Smart Citations
“…This result is in agreement with past measurements of slip band length in coarse grain RR1000 materials. 22 Moreover, these observations are consistent with the fatigue modeling results, whereas the formation of longer PSBs represented a higher degree of stored energy and were attributed to a shorter fatigue life. 22 Lastly, fatigue crack initiation has been observed extensively throughout the years at or near twin boundaries, stemming back to the work of Boettner et al 28 and Thompson 29 and more recently in Nibased superalloys.…”
Section: Strain Mappingsupporting
confidence: 86%
“…22 Moreover, these observations are consistent with the fatigue modeling results, whereas the formation of longer PSBs represented a higher degree of stored energy and were attributed to a shorter fatigue life. 22 Lastly, fatigue crack initiation has been observed extensively throughout the years at or near twin boundaries, stemming back to the work of Boettner et al 28 and Thompson 29 and more recently in Nibased superalloys. 24,30,31 Moreover, there exists a high prevalence of annealing twin boundaries inherent to Ni-based superalloys, such that the majority of cracks initiate due to twin boundaries.…”
Section: Strain Mappingsupporting
confidence: 86%
See 2 more Smart Citations
“…The process parameters were selected based on a process deformation map to identify pertinent microstructural features, as discussed further in Detrois et al 33 The γ 0 precipitate structure of the RR1000 variants was revealed by etching with a modified Kallings reagent, by EOS Laboratories, which etched the γ phase. The underlying γ 0 structures were imaged on a FEI Quanta 3D field emission gun (FEG) dual-beam scanning electron microscopy (SEM), as shown in Figure 1A,B.…”
Section: Experimental Methodsmentioning
confidence: 99%